Thermoelectric generator : experimental investigation and performance analysis - Tee, Jonathan Li Wei (2014)
Discovered in the 19th century, thermoelectric power generation converts heat into electrical power. It was then thought that its low efficiency could not be further improved due to the material’s figure of merit, a material property that controls the efficiency. Presently, due to the global demand for sustainable energy sources coupled with the advancement of technology, new thermoelectric materials with better figure of merit were created and thermoelectric power generation was seen as a viable source to harness waste heat into useful energy. This saw the rise in interest in thermoelectric power generation.